Nutrient profiling and degree of food processing of child-targeted packaged foods in Türkiye: An urgent call for policy action - Lütfiye Parlak-Yetişen; Derya Dikmen (PLoS ONE, 2025)
This study aimed to evaluate the nutritional quality and degree of processing of packaged foods and beverages marketed to children in Türkiye using nutrient profiling models and the NOVA classification. A cross-sectional study was conducted by collecting packaging and label data from child-targeted food and beverage products available in grocery stores.The study was carried out in 23 grocery stores in Ankara, Türkiye. A total of 775 packaged food and beverage products marketed to children aged ≥3 years were analyzed. The products were assessed for compliance with four different nutrient profile models (NPMs) and classified according to the NOVA food processing system. Findings indicate that 93.2% of products did not comply with the WHO NPM-2023 criteria and should not be marketed to children. Additionally, the majority of these products were classified as Nutri-Score groups D and E (70%) and ultra-processed (92.7%). Ultra-processed foods had a significantly lower nutritional quality (p < 0.001) according to the Nutri-Score. A significant difference was observed between NOVA classification and product categorization under the NPMs (p < 0.001). Most packaged foods and beverages marketed to children in Türkiye are ultra-processed and nutritionally inadequate. According to WHO and other NPMs, these products should not be marketed to or consumed by children. There is an urgent need for policy interventions to restrict the marketing of unhealthy packaged foods targeted at children.